Agricultural policy frameworks and the agricultural sector in Uganda: Analysis of the plan for modernisation of agriculture - Mwesigwa, David; Oguta, James; Acanga, Alfred (International Journal of Pure Agricultural Advances, 2023)
The aim of this study was to evaluate the Plan for Modernization of Agriculture’s effectiveness and offered suggestions. Accessible literature has chosen to deliberately modernize agriculture and acknowledged the necessity to emphasize poverty reduction as a key component. The method for this paper was a review of secondary data on accessible empirical as well as conceptual resources on the agricultural policy frameworks in Uganda encompassing the gathering of information from obtainable resources. The findings suggest that agricultural policy frameworks are essential for fostering transformation in the industry. Prior efforts to combat poverty have concentrated on the policy content and disregarded other factors, such as community livelihoods. The study assumes collaborative arrangement between local stakeholders, including those who might otherwise be targeted, in determining the success (or failure) of prior interventions and training them to deal with the problems that have hampered their effectiveness. It can be noted that for Uganda’s agricultural transformation to be successful, a thorough study should be made of all the policies that have been put in place since 2000.